(untitled) (Academic Journal of Internal Affairs, 2018)
The author shows how the emergence of new forms of cybercrime is caused by the artificially created cognitive entities, the narrow knowledge-based AI penetration. With this technology leap, cybercrime is transformed into a qualitative change that means a previously unheard of threat.